Trace and Rare Earth elements and Hf isotopic composition of zircons from the Paleoproterozoic diorite-granodiorite plutons of the Kursk block, Sarmatia as their petrogenesis indicators (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: Lu-Hf isotopic composition of zircons from the calc-alkaline diorite-granodiorite plutons of the Stoilo-Nikolaevsky complex in the Kursk block is an important indicator of the petrogenesis and tectonic environment of their formation. Methodology: We carried out the study of Lu-Hf isotopic composition of zircons and the analysis of the Ti and other elements concentrations. Results and discussion: Morphological features, Th/U ratio, rare earth elements distribution and high crystallization temperatures according to the Ti-in-Zrn thermometer are the evidences of its magmatic nature. Isotopic Hf composition is the evidence of heterogeneous, primarily Paleoarchaean sources with wide variations of the εHf(T) values and model ages. Conclusion: Diorite-granodiorite massifs were formed in the back-arc environment on the thickened ancient continental margin.
Keywords: Kursk block; Lu-Hf isotopy; zircon; petrogenesis